Chylous Ascites in Systemic Lupus Erythematosus (SLE) Patients - Da Silva Domingues, Vital Manuel; Da Silva Domingues, Vital; Neves, Isabel; Garrido, Susana; Ferreira, Inês; Mendonça, Teresa (European Journal of Case Reports in Internal Medicine, 2015)
The gastrointestinal system is commonly implicated in Systemic Lupus Erythematosus (SLE). Ascites, produced by several mechanisms has been reported as a systemic manifestation of lupus, but only rarely as an initial presentation of the disease. Its appearance is often insidious and without abdominal pain. Chylous ascites (such as chyle in the peritoneal cavity) has seldom been reported in SLE. We describe a case of chylous ascites in an SLE patient, reviewing the other published cases, its pathophysiology and its management.